2021
DOI: 10.18203/2394-6040.ijcmph20210028
|View full text |Cite
|
Sign up to set email alerts
|

Management of post-operative sore throat in patients undergoing endotracheal intubation: literature review

Abstract: Postoperative sore throat (POST) is a common complaint that is classified as the 8th most undesirable events after general anesthesia. Endotracheal intubation has been estimated to be the commonest factor causing POST. We aim to review the risk factors and preventive measures to reduce the incidence and severity of POST following endotracheal intubation. Although sore throat can be induced by many perioperative factors, endotracheal intubation remains the commonest cause that can induce endothelial injury and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…But the relation is contradictory; including age (Compared to younger patients, older patients had more POST [4,24]. In contrast other studies showed greater incidence in younger patients as compared to older counterparts [9,14]; sex (higher in female than males [4,5,9,10,[33][34][35]. Unlike the mentioned researches, this study showed no significant association between POST and three socio-demographic factors (age, sex and BMI).…”
Section: Factors Associated To Post Operative Sore-throatmentioning
confidence: 54%
See 2 more Smart Citations
“…But the relation is contradictory; including age (Compared to younger patients, older patients had more POST [4,24]. In contrast other studies showed greater incidence in younger patients as compared to older counterparts [9,14]; sex (higher in female than males [4,5,9,10,[33][34][35]. Unlike the mentioned researches, this study showed no significant association between POST and three socio-demographic factors (age, sex and BMI).…”
Section: Factors Associated To Post Operative Sore-throatmentioning
confidence: 54%
“…A number of factors, some avoidable, influence the incidence and extent of postoperative sore throat, but it is unlikely that this problem will ever be completely eliminated [5]. Overall; Instrumentation of the airway is an inherent risk factor for the development POST [9] . It is widely accepted that some complications related delivery of anesthesia care is inevitable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation